The CBM-opathies—A Rapidly Expanding Spectrum of Human Inborn Errors of Immunity Caused by Mutations in the CARD11-BCL10-MALT1 Complex - Lu, Henry Y.; Bauman, Bradly M.; Arjunaraja, Swadhinya; Dorjbal, Batsukh; Milner, Joshua D.; Snow, Andrew L.; Turvey, Stuart E. (Frontiers in Immunology, 2018)
The caspase recruitment domain family member 11 (CARD11 or CARMA1)—B cell CLL/lymphoma 10 (BCL10)—MALT1 paracaspase (MALT1) [CBM] signalosome complex serves as a molecular bridge between cell surface antigen receptor signaling and the activation of the NF-κB, JNK, and mTORC1 signaling axes. This positions the CBM complex as a critical regulator of lymphocyte activation, proliferation, survival, and metabolism. Inborn errors in each of the CBM components have now been linked to a diverse group of human primary immunodeficiency diseases termed “CBM-opathies.” Clinical manifestations range from severe combined immunodeficiency to selective B cell lymphocytosis, atopic disease, and specific humoral defects. This surprisingly broad spectrum of phenotypes underscores the importance of “tuning” CBM signaling to preserve immune homeostasis. Here, we review the distinct clinical and immunological phenotypes associated with human CBM complex mutations and introduce new avenues for targeted therapeutic intervention.